Financial development, foreign trade, regional economic development level and carbon emissions - Sun, Yongchun (Frontiers in Environmental Science, 2022)
Drawing on balanced panel data of 30 Chinese provinces in 2000–2020, this paper uses the Panel Smooth Transformation Regression (PSTR) model to explore the impact of financial development and foreign trade on carbon emissions under different regional economic development levels. The empirical results show that: 1) Financial development and foreign trade have a non-linear impact on carbon emissions under different economic development levels; 2) As the level of economic development exceeds the threshold, the positive effect of financial development on carbon emissions will weaken, while the effect of foreign trade on carbon emissions will change from negative to positive; 3) The sub-sample estimates further found that the impact on carbon emissions in southern and northern regions are different. The threshold in the south is lower than that in the north, but all the conversion speed is faster.